Comparison of intelligent development (IQ & EQ) of children with cleft lip and palate - Rasool Esmaeili Maryan; Masood Feizbakhsh; Zohreh Esmaeilian; Golnoosh Sedaghati (Wolters Kluwer Medknow Publications, 2024)
Background: Attention to the issue of intelligence and its promotion in children with cleft lip and cleft palate (CL and CP) is necessary to reduce their injuries in life. This study aimed to determine the intelligence quotient (IQ) and emotional intelligence (EQ) in children with CL and CP in comparison to healthy children. Materials and Methods: In this descriptive study, 140 children, including 70 children with CL and CP, were selected from the Children treated in Craniofacial and Cleft Research Center, Spearman correlation, ANOVA and 70 healthy children were selected from the Pediatric Dentistry Department of Isfahan University, in the age range of 5-9 years. After obtaining the consent of the children's parents, the Raven IQ questionnaire and the Mayer and Salovey EQ questionnaire were given to the children. Data were analyzed by the Pearson correlation coefficient tests (α =0.05). Results: EQ score in healthy children was significantly higher than in children with CL and CP (P < 0.001). The percentage of IQ cognitive intelligence in healthy children and children with CL and CP was not significantly different (P = 0.641). In healthy children, no significant relationship was observed between cognitive intelligence IQ and EQ (r = 0.018, P = 0.882). However, among children with CL and CP, there was a significant inverse relationship between cognitive intelligence IQ and EQ (P < 0.001, r = −0.526). Conclusion: CL and CP have no effect on IQ in children, but it does affect EQ.